Rancang Bangun Sistem Inventory ATK dengan UML dan Object Oriented Program - Anita Diana; Indah Puspasari Handayani (Ikatan Ahli Informatika Indonesia, 2019)
Office stationery procurement information system in each agency has a dynamic nature. Barriers to the work of an information system management flow can be fatal in a decision making and operational performance of an agency. The number of human resources in an agency will greatly affect the needs of stationery in daily work activities because it is a basic need in the world of work. When miscalculations occur, a long processing time and a lack of information generated, can affect cooperation with suppliers and state expenditure through the state treasury service office. Office stationery procurement system consists of many interconnected objects, the OOP (Object Oriented Programming) method that has a programming pattern based on the object concept is the right method to respond to these problems. In addition, the method is flexible in the sense that it will be easy to change, develop and maintain. The process of making the system starts from analyzing the system that is running and developed into a new system, using the programming language VB.net and MySQL-Front as a data storage. It is expected that with the construction of an office stationery procurement information system, it can run smoothly, so that recording, calculating and storing data is easier and does not require a long time.